İnsan büyüme hormonunun (BH-N) klonlanması, ekspresyonu ve izole büyüme hormonu eksikliği sendromunun genetik karakterizasyonu - Çoker, Ajda (My University, 2009)
CLONING AND EXPRESSION OF THE HUMAN GROWTH HORMONE (GH-N) AND GENETIC CHARACTERIZATION OF THE ISOLATED GROWTH HORMONE DEFICIENCY SYNDROME Growth hormone (GH) which has an effect on postnatal growth was sometimes deficient both in children and adults leading Growth Hormone Deficiency Syndrome (GHD). Recombinant GH (rGH) is used as a treatment for these cases. In order to produce rGH in our country, we isolated RNA from blood and cloned GH cDNA and rGH was expressed in bacteria as a fusion protein with Gluthatione S-Transferase. It was purified and biological activity was shown in ex vivo. Genomic GH gene was cloned from genomic DNA isolated from blood and expressed in mammalian cells. Isolated Growth Hormone Deficiency (IGHD) is a medical condition of insufficient production of growth hormone (GH) that is caused by mutations on GH-N gene in different ethnic origin children. In order to screen GH-N gene mutations in Turkish IGHD children; we isolated genomic DNA from 76 children’s blood. Macrodeletions on GH-N gene were detected by PCR, microdeletions and insertions and nucleotide substitutions were detected by DNA sequencing of PCR products. 6.6 kb macrodeletion including only GH-N gene, Glutamic acid to Glysine (E33G), Asparagine to Aspartic acid (N47D), Threonin to Alanin (T-24A) missense mutations in heterozygote state and one missense mutation Alanine to Serine (A13S) substitution and one nonsense mutation Tryptophane to stop codone (W-7X) in homozygous state were observed. GAAA insertion in intron 1 of GH-N gene and both intron 1 (+83C) deletion and deletion of 166. amino acid of GH protein phenilalanin (F166Del) mutations were detected. Mutant GH-N genes including these mutations were cloned and functional analysis of mutations were detected by binding of GHR with mutant GH by lusiferase assay. It has been observed that W-7X, E33G, F166Del, A13S and N47D mutations lead to a decrease in GH biological activity. However T-24A, GAAA insertion and deletion of +83C mutations have no biological activity disfunction.
Keywords: Biyoloji; Hormonlar